An effective PSO based cascaded H-bridge multilevel inverter STATCOM with reduced number of materials count. (2021) - Gaur, Parul; Pal Verma, Yajvender; Singh, Preeti
Abstract: Medium voltage and high power multilevel inverters are nowadays widely used for reactive power compensation applications. Multilevel inverters based Static Synchronous Compensator (STATCOM) devices makes the power system more feasible due to the benefits offered by the multilevel inverters such as output voltage with lower harmonics, high modularity, and high-power quality in the output. This paper presented an effective Particle Swarm Optimization (PSO) algorithm based cascaded H-bridge multilevel inverter STATCOM with reduced number of materials count. The materials used for the semiconductor devices are the Insulated Gate Bipolar Transistors (IGBTs). These IGBTs are fired using the optimized switching angles, which further leads to minimum total harmonic distortion. PSO technique is being used for the calculation of optimized switching angles. Further, the performance of PSO based multilevel inverter with STATCOM is investigated by calculating the harmonics reduction and total harmonic distortion.